Analisis Penerapan Pernyataan Standar Akuntansi Keuangan No. 44 - Akuntansi Aktivitas Pengembangan Real Estat - Baridwan, Zaki (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2006)
Based Financial Accounting Standar No. 44, there are four methods recognition revenue, which can be able to recognizes real estate sales transaction. The methods are (i) full accrual method; (ii) finished persentation method; (iii) deposit methods; and (iv) lease method. Thus, objective this research are (i) seeking method which be choosen by real estate corporate in revenue recognition, include expense recognition; (ii) seeking method, which used relevant with Financial AccountingÂ Standard No. 44; and (iii) seeking justification used that method. Key words: Revenue Recognition, Expense Recognition, Matching Deposit